Tourist attractiveness of Venice in Żnin district - Gotowski, Rafał; Parzych, Krzysztof (Journal of Education, Health and Sport, 2016)
The article concerns the tourist attractiveness of Venice, a small town in northern Poland with a rich historical past associated with the Middle Ages and the beginnings of railway transport. The aim of this work was the identification of the main symbols of this part of the Polish, identification of tourist attractions of Venice, and the determination of the attractiveness degree of the various tourist attractions located in the village and defining directions of further development of the tourist offer. Based on the survey, it was found the most important symbol of this polish tourist region is the Archaeological Museum in Biskupin. The main attraction of Venice is the Narrow Gauge Railway Museum and the Castle ,,Bloody Devil" which is mostly visited during the waiting for the train arrivals or is overlooked by tourists.